LINHAS DA POLÍTICA EXTERNA CULTURAL ALEMÃ COMO BASE DA COOPERAÇÃO EDUCACIONAL COM O BRASIL - Voerkel, Paul (Ecos de Linguagem, 2019)
Language issues have become overwhelmingly important during the last few years – not only in the scientific scale, but as well as a political priority. While language policy appears to be a quite recent topic in the case of Brazil, Germany counts on a longer tradition to consider culture and language as instruments for international cooperation. The present article starts with a historical overview of the history of German cultural policy on an international level, reveals its relevant structures, goals and challenges and ends with a short comparison of some related aspects in nowadays Brazil. The general reflections about the influence of public policy on the study field of Humanities (and here specifically on graduation courses of languages and culture) are considered to be valid both for language teachers and those enrolled with educational & language planning and curriculum design.